Synergistic Treatment with Antiretrovirals and Laser Interstitial Thermal ThErapy (STARLITE) for unresectable glioblastoma: A phase 1 study protocol - Manav Daftari; Christian K. Ramsoomair; Daniel Aaronson; Deepa Seetharam; Emily A. Andreae; Leonela Wright; Sunwoo Han; Jay Chandar; Victor Lu; Vaidya Govindarajan; Michael E. Ivan; Ricardo J. Komotar; et al. (PLoS ONE, 2025)
Glioblastoma (GBM) is the most common form of primary adult brain tumor with a five-year survival of <7%. Standard of care (SoC) involves maximal safe surgical resection with chemoradiation; nevertheless, most patients experience disease progression. Deep intracranial GBM is unresectable, limiting treatment to chemoradiation only. Thus, novel approaches are needed. Laser interstitial thermal therapy (LITT) is a promising minimally invasive procedure using thermal energy for focal necrosis. Another approach is antiretroviral therapy (ART), which was initially explored as a treatment for acquired immunodeficiency syndrome (AIDS)-related malignancies, that has recently shown preclinical promise for GBM. We present the Synergistic Treatment with Antiretrovirals and Laser Interstitial Thermal ThErapy (STARLITE) (NCT06428045) trial, which seeks to synergize LITT with ART to treat unresectable GBM. STARLITE is a single-institution, single-arm, phase 1 study. An ART regimen of abacavir, lamivudine, and ritonavir will be administered followed by SoC adjuvant therapy in patients with newly-diagnosed, unresectable GBM after LITT. The primary objective of the study will be the determination of the maximum tolerated dose (MTD) and/or recommended phase 2 dose (RP2D) of ritonavir as part of the ART regimen. Secondary objectives of the clinical trial will be to estimate progression-free survival (PFS) and overall survival (OS). LITT has been shown to have minimal post-operative complications while improving OS in unresectable GBM. In preclinical GBM models, ART has been shown to reduce cell viability and stemness. STARLITE aims to leverage the ability of LITT to target unresectable GBM foci and transiently open the blood-brain barrier (BBB) to increase the tumoral delivery of ART and augment its anti-tumor effects. We hypothesize this combination will be well-tolerated with minimal adverse effects and improve GBM prognosis. Trial Registration This clinical trial is registered on ClinicalTrials.gov (NCT06428045). The authors confirm that all ongoing and related trials for this intervention are registered.